A quasi-dimensional model of turbulence and global charge motion for spark ignition engines with fully variable valvetrains. (October 2014) - Grasreiner, Sebastian; Neumann, Jens; Luttermann, Christoph; Wensing, Michael; Hasse, Christian
In this article, a new in-cylinder turbulence modeling approach aims at the improvement of quasi-dimensional simulations for modern spark ignition engines with fully variable valvetrains. Within the derived quasi-dimensional turbulence model, the turbulent production term can physically react on a change of engine operation (e.g. intake valve lift, intake valve timing, engine speed and boost pressure). Moreover, the approach offers access to detailed charge motion quantities for the first time in quasi-dimensional calculations. Hence, it is able to satisfy qualitative and quantitative turbulence descriptions within the entire operating range of the engine.